WAWASAN BRUNEI 2035: A NATIONAL NARRATIVE OF MODERNITY IN TRADITIONAL NORMATIVITY - Pawiro, Suyanti Adi (International Review of Humanities Studies, 2021)
Brunei Darussalam maintains its absolute monarchy system by integrating its well-established Islamic values into national ideology while calculating strategic plans to progress. Wawasan Brunei 2035 embodies collective national objectives that tie Brunei together as a nation amidst the future’s challenges. This pathway is viewed as a paradox of modernity and tradition. Using a qualitative method, this study provides perspectives on how Brunei Darussalam maintains its unique political stand in this fashion by looking into its formation of national identity and examining Wawasan Brunei 2035 as a national narrative. The study finds that Wawasan Brunei 2035 guides the nation and keeps it on track to retain its prosperity. As the idea of progress is translated into this development vision, Brunei carefully selects the element of modernity to sustain its standing.